Karakteristik Sosial Ekonomi Nelayan Pemanfaat Hiu Tikus (Alopiidae) di Manggis, Karangasem, Bali - Hanifa Miranda I.H. Putri; I Wayan Arthana; Elok Faiqoh; Ranny R. Yuneni; Yuniarti K. Pumpun (Fakultas Kelautan dan Perikanan Universitas Udayana, 2022)
Thresher sharks are known to have substantial economic value. They are caught globally as target and as bycatch in tuna fisheries. Due to their declining population, they are listed as an appendix II species on CITES, therefore any form of trade and fisheries related to the species have been nationally and internationally regulated. However, information on thresher shark fisheries in Bali is still limited. This study aims to socio-economically characterize thresher shark fishermen in Manggis, Karangasem. The research was conducted in August 2020 – October 2020 by interviewing 53 out of 119 recorded shark fishermen using a structured questionnaire. Shark fishermen use surface longlines to catch thresher sharks (Alopiidae) in between 3 areas, North Nusa Penida-Karangasem, east Nusa Penida and Bangko-Bangko. The fishermen catch sharks exclusively during the months of June-October and catch tuna the rest of the year. Operational costs for 1 boat ranges between Rp 121.000 – Rp 250.000 during 1 round trip. The income generated from shark fishing each trip averages to about Rp 627.714 per boat. Prior to the Covid-19 pandemic, some of the fishermen work jobs in the tourism sector. However, due to the pandemic’s impact on tourism, they have no choice but to be fishermen full time. Although thresher shark fisheries in Manggis are generally small scale, conservation and management strategies need to be implemented to ensure sustainable use of shark resources.